2015
DOI: 10.1302/0301-620x.97b10.35303
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopy of the hip for patients with mild to moderate developmental dysplasia of the hip and femoroacetabular impingement

Abstract: The purpose of this study was to determine patient-reported outcomes of patients with mild to moderate developmental dysplasia of the hip (DDH) and femoroacetabular impingement (FAI) undergoing arthroscopy of the hip in the treatment of chondrolabral pathology. A total of 28 patients with a centre-edge angle between 15° and 19° were identified from an institutional database. Their mean age was 34 years (18 to 53), with 12 female and 16 male patients. All underwent labral treatment and concomitant correction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 34 publications
2
56
0
Order By: Relevance
“…2) [6,13,27,34,43]; and (10) headneck offset ratio (HNOR) was measured by taking the femoral head-neck offset measurement and dividing by the femoral head diameter [6,10,34]. Hips with an alpha angle C 55°were classified as having coexisting cam morphology [16,31,37]. We further assessed subgroups to try to identify relationships between proximal femoral characteristics and head-neck offset abnormalities.…”
Section: Methodsmentioning
confidence: 99%
“…2) [6,13,27,34,43]; and (10) headneck offset ratio (HNOR) was measured by taking the femoral head-neck offset measurement and dividing by the femoral head diameter [6,10,34]. Hips with an alpha angle C 55°were classified as having coexisting cam morphology [16,31,37]. We further assessed subgroups to try to identify relationships between proximal femoral characteristics and head-neck offset abnormalities.…”
Section: Methodsmentioning
confidence: 99%
“…Fukui et al similarly recently reported the results of 28 patients with mild-to-moderate hip dysplasia and concomitant femoroacetabular impingement (FAI) undergoing hip arthroscopy. 25 This was a select group of patients from the practice of the senior author of that paper that had either labral repair or reconstruction, with all other patients with labral debridement excluded. All these patients had radiographic signs of hip dysplasia, with half of them having signs of acetabular retroversion and combined femoral head neck abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Hip arthroscopy has a dual role regarding the treatment of hip microinstability. The correction of borderline dysplastic characteristics, that may contribute to microinstability, in combination with the manipulation of soft tissues in and around the hip joint are responsible for the encouraging results that has already been reported in literature 49,50 . Intra-articular pathology, such as labral tears, cartilage defects and/or ligamentum teres abnormalities are often present in patients with hip microinstability.…”
Section: Treatmentmentioning
confidence: 90%